2018
DOI: 10.1002/csr.1669
|View full text |Cite
|
Sign up to set email alerts
|

Diversity in the workplace: An overview of disability employment disclosures among UK firms

Abstract: People with disabilities (PWDs) defined as the world's largest minority stakeholder group continue to face significant barriers to labor market entry and corporate inclusion. The associated social and economic costs of supporting non-working PWDs can be high and long term. Yet, their potential contribution and impact on human capital, firm productivity, and the innovative capacity of business entities are valuable but underutilized. The employment of PWDs has institutional and managerial implications for equit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
49
0
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(54 citation statements)
references
References 90 publications
(103 reference statements)
0
49
0
5
Order By: Relevance
“…Empirical findings suggest that employees with disabilities have higher levels of motivation, productivity, job retention level and lower occupational accident rates compared to those who do not have any disabilities (Khan et al, 2019). Therefore, companies should be more flexible in relation to the individual needs of people with disabilities so that they can enable a more effective participation of these workers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Empirical findings suggest that employees with disabilities have higher levels of motivation, productivity, job retention level and lower occupational accident rates compared to those who do not have any disabilities (Khan et al, 2019). Therefore, companies should be more flexible in relation to the individual needs of people with disabilities so that they can enable a more effective participation of these workers.…”
Section: Discussionmentioning
confidence: 99%
“…It is estimated that 80% of the people with disabilities live in developing countries and 20% of the poorest people have a disability. It is common among economic and cultural norms that the people with disabilities remain highly vulnerable, regardless of whether the state adopts an individual or social governance model (Khan et al, 2019). Life opportunities for women and children with disabilities have remained low in many countries (OCDE, 2018;WHO, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Airlines' fund-raising to support the welfare of children, namely UNICEF's Change for Good (CFG) program, by encouraging passengers' donation of spare foreign currency on flights can be one of many examples in the field of hospitality [41]. People with disabilities are regarded as the world's largest minority [3], and sufficient statistics showed that employing people with disabilities were largely overlooked [6][7][8]. With respect to this, involving disabled people in the labor market is a good deed reflecting PCSR as it promotes an inclusive culture and recognizes the diversity in the workplace.…”
Section: Corporate Social Responsibility (Csr) and Philanthropic Csr mentioning
confidence: 99%
“…Such individuals face various barriers that restrict them from participating in a local community or a larger society on an equal basis with others [1,2]. Particularly, the disabled are considered as the world's largest minority in the labor market [3]. With this respect, unceasing efforts were made to promote the concept of equal opportunities and increase the hiring of those with disabilities.…”
Section: Introductionmentioning
confidence: 99%
“…While PWDs continue to face significant barriers to the inclusion in the labor market and society, their potential contributions in terms of human capital, business productivity, and innovative capacity are considered to be valuable [ 19 , 20 ]. Fomenting the employment of PWDs is considered as crucial for equality of opportunity, social mobility, and workforce diversity [ 19 ].…”
Section: Introductionmentioning
confidence: 99%